A comprehensive dynamic efficiency-enhanced energy management strategy for plug-in hybrid electric vehicles. (1st August 2019) - Wang, Feng; Zhang, Jian; Xu, Xing; Cai, Yingfeng; Zhou, Zhiguang; Sun, Xiaoqiang
Highlights: Dynamic transmission efficiency model of planetary coupling transmission system. Dynamic efficiency optimization strategy considering fatigue life of powertrain. Optimized vibration-induced energy management strategy designed and tested. Abstract: This paper presents a comprehensive dynamic efficiency model for the overall powertrain efficiency that considers the internal combustion engine and electric motor generators in depth as well as a planetary coupling transmission system of PHEVs example. In particular, the dynamic forces of planetary coupling transmission system with an effect on the dynamic transmission efficiency are taken into consideration. Then a dynamic efficiency optimization strategy is proposed to improve the fuel economy, and an improved dynamic efficiency optimization strategy, consisting in adding to the dynamic efficiency optimization strategy a penalty coefficient, is applied to reach the trade-off between energy consumption and fatigue life of planetary coupling transmission system. Eventually, the dynamic efficiency optimization strategy and improved dynamic efficiency optimization strategy are validated by hardware-in-the-loop experiments. The main contribution of this study is to explore a novel way to optimize the comprehensive dynamic efficiency of whole powertrain, and also improve ride comfort by avoiding planetary coupling transmission system working in the inefficient resonance region.